Cerebrospinal fluid kappa and lambda free light chains in oligoclonal band‐negative patients with suspected multiple sclerosis. (2nd December 2019) - Ferraro, D.; Trovati, A.; Bedin, R.; Natali, P.; Franciotta, D.; Santangelo, M.; Camera, V.; Vitetta, F.; Varani, M.; Trenti, T.; Gastaldi, M.; De Biasi, S.; et al.
Abstract : Background and purpose: Cerebrospinal fluid (CSF) kappa free light chains (FLCs) may be a more sensitive marker of intrathecal immunoglobulin (Ig)G synthesis compared with oligoclonal bands (OCBs). Our aim was to retrospectively determine the additional value of the kappa and lambda index (CSF FLC/serum FLC)/(CSF albumin/serum albumin) in predicting a multiple sclerosis (MS) diagnosis in a group of OCB‐negative patients with suspected MS. Methods: The CSF and serum kappa and lambda FLCs were tested using the Freelite kit (serum) and Freelite Mx (CSF) assay (The Binding Site Group, Bimingham, UK) in 391 OCB‐negative patients with suspected/possible MS and in 54 OCB‐positive patients with MS. Results: The CSF kappa FLC levels were below the detection limit (0.27 mg/L) in 61% of patients. Using quantitative data, we found the best kappa index cut‐off value for the prediction of MS to be 5.8. A kappa index ≥5.8 was present in 25% of OCB‐negative MS (23/92) and in 98% of OCB‐positive patients with MS. Using a qualitative approach and a kappa index cut‐off of 5.9, based on literature data, we likewise found that 24% of OCB‐negative patients with MS had a kappa index ≥5.9, compared with 5.4% of OCB‐negative patients without MS ( P < 0.001). No reliable data could be obtained for the lambda index; lambda FLCs were below the detection limit (0.68 mg/L) in 90% of CSF samples. Conclusions: The kappa index could contribute to the identification of OCB‐negative patients with a high probability of an MS diagnosis. Using more sensitive techniques might even improve the diagnostic performance of the kappa index and better define the role of the lambda index.